Microbial contamination in herbal medicines: a serious health hazard to elderly consumers - de Sousa Lima, Carolina Miranda (BMC Complement Med Ther, 2020)
INTRODUCTION: The use of herbal medicine is on the rise worldwide, and safety issues associated with herbal medicines may have an exacerbated impact in elderly because this population has an increased susceptibility and sensitivity to health complications due to the aging process. METHODS: This cross-sectional study was carried out at a primary health care unit in the city of Macapa, Brazil. The herbal medicines used and the sociodemographic characteristics of 123 voluntarily consenting participants were collected using a structured questionnaire. A total of 132 herbal medicines with oral or topical administration were donated by the elderly for microbial analysis before consumption, and 18 water samples used in the preparation of homemade herbal medicines were collected. Bacterial and fungal counts and identification of bacterial pathogens (Escherichia coli, Salmonella spp., Pseudomonas aeruginosa and Staphylococcus aureus) were performed according to the regulations of the Brazilian Pharmacopoeia and World Health Organization. Water analysis for the detection of coliforms and E. coli was carried out using Colilert® according to the manufacturer’s instructions and the techniques established by Standard Methods. RESULTS: Of the study participants, 78.8% were women. Bacterial growth was observed in samples from 51.5% of study and 35.6% had fungal growth. A total of 31.8% of the herbal medicine samples exceeded the safety limits (CFU/g ≤ 10(5)), including 16.7% of the homemade herbal medicines and 15.1% of the commercial herbal medicines. It was also found that 31.0% of the samples exceeded the safety limit for fungal growth. The microorganisms most commonly isolated from the herbal medicines were S. aureus (49.2%), followed by Salmonella spp. (34.8%), E. coli (25.8%), and P. aeruginosa (14.4%). Of water samples analyzed, 77.8% were positive for total coliforms (1 ml) and in 66.7% water samples E. coli was detected (1 ml), making them unfit for consumption. CONCLUSIONS: The use of homemade and commercial herbal medicines is a major risk to the health of elderly who use these therapies due to the lack of microbial quality standards. We observed levels of viable bacteria and fungi that were above safety limits; in addition, we were able to isolate pathogenic bacteria from these herbal medicines.